Onkozytäre Tumoren der Niere – neue Differenzialdiagnosen - Polifka, Iris; Ohashi, R.; Moch, H. (Pathologe, 2021)
Background: Recent developments in differential diagnosis have led to new knowledge about oncocytic renal neoplasms. Objectives: Overview of differential diagnosis of oncocytic tumours. Materials and methods: We performed a literature search on oncocytic renal tumours and mapped known tumour types. Possible differential diagnoses are discussed. Results: Besides the tumour types already acknowledged by the 2016 WHO classification, there is new evidence regarding the group of hard-to-classify oncocytic neoplasms. Findings point to immunohistochemical and molecular characteristics that may lead to the establishment of new entities in the future. In addition, important differential diagnosis can now be identified, facilitating specific therapies for oncocytic renal tumours. Conclusion: A correct diagnosis of oncocytic renal tumours not only improves prognostic assessment (and, if necessary, specific therapies) but is also clinically relevant regarding a possible association with hereditary tumour syndromes.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Chromophobe renal cell carcinoma; ESC; MTOR; Oncocytoma; SDH